The Nexus of Comorbid Thyroid Dysfunction, Developmental Trauma, and Marital Distress in Severe Depression: A Case Study of an Integrative Bio-Psycho-Social-Spiritual Approach - I Putu Roni Mahendra Putra (HM Publisher, 2025)
Background: The management of major depressive disorder (MDD) is frequently complicated by the presence of medical comorbidities and profound psychosocial stressors. This complexity creates a significant risk for